Early Adults Coping Skills and Post Traumatic Stress Disorder After Eruption of Semeru Mountain: a Cross-sectional Study - Zainuri, Ahmad; Setioputro, Baskoro; Yunanto, Rismawan Adi (Jurnal Kegawatdaruratan Medis Indonesia, 2024)
Post Traumatic Stress Disorder (PTSD) is a psychiatric disorder that can occur in people who have experienced or witnessed a traumatic event. This study aims to analyze the relationship between coping skills and post-traumatic stress disorder after the eruption of Mount Semeru in early adults in Sumber Wuluh Village, Lumajang. Using a cross sectional study method, the subjects of this research were early adults (26-35 years old) with a sample of 138 respondents. Sampling uses Cluster Sampling. The results characteristics respondents in study were early adults aged 26-35 years, the gender group was mostly female, and the education level was mostly elementary and middle school. The coping skills in this study used adaptive coping (65.2%). Post traumatic stress disorder in this study, famale experienced more PTSD (28.3%), and male did not experience PTSD (25.4%). The relationship between coping skills and post-traumatic stress disorder was obtained with a P-value of 0.000, less than ɑ <0.05. It can be concluded that there is a relationship between the two variables, and has a correlation value of -.622. A negative correlation means that the lower the coping skills score, the higher the post-traumatic stress disorder score. It can be concluded that coping skills and post-traumatic stress disorder have a significant relationship with a negative direction.